PENGARUH SINAR LAMPU INFRA MERAH TERHADAP PENYEMBUHAN LUKA RUPTUR PERINEUM PADA IBU NIFAS PRIMIPARA DI RUMAH SAKIT UMUM AL-FATAH AMBON - Ratna Malawat (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2017)
Infrared light on the skin activates the water molecules in the skin as the infrared mengadung has the same vibration of water molecules. The aim of the research is to determine the effect of a 60-watt lamp light on the healing of perineum rupture healing of primiparous post partum mothers in Al-fatah regional public hospital of Ambon. The research was a pre-experiment of static group comparison. The sample was selected using purposive sampling method consisting of 40 people divided into two groups. The data were obtained through observation (checklist). They were analyzed using Mann Whitney. The result of the research indicate that there is a significant difference between treatment group and control group with a value of p=0.00. The components of injury assessment are redness with a value of p=0.30 and discharge with a value of p=0.12 there is no significant difference between redness and discharge of treatment group and control group. Assessment was also done for edema, ecchymosis, and apporaximation with a value of p=0.00. There is a significant difference between treatment group and control group of the there components, i.e. edema, ecchymosis, and apporaximation. There is also a significant difference of wound healing treatment between treatment group and control group with a value of p=0.01. The perineum rupture healing process is faster in primiparous post partum mothers using a infrared lamp light compared to primiparous post post- partum mothers without using a infrared lamp light.